Nitric oxide metabolites in the lumbosacral spinal cord interstice and cerebrospinal fluid in female rats with acute cyclophosphamide-induced cystitis. An in vivo microdialysis study - Rocha, Jeova Nina (Einstein (Sao Paulo), 2013)
OBJECTIVE: To determine the concentration of nitrate/nitrite in the cerebrospinal fluid and in the dorsal horn interstice of the L6-S1 spinal cord boundary in rats with or without cystitis induced by cyclophosphamide. METHODS: All experiments were conducted using Wistar female rats. A microdialysis probe was implanted in the subarachnoid space or in the spinal cord tissue at the L6-S1 segments (confirmed histologically). Two days later, the microdialysis probe was perfused with artificial cerebrospinal fluid, containing or not NGmonomethyl-L-arginine. Samples were collected every 15 minutes and kept at −20°C. Nitrite/nitrate concentrations were determined by chemiluminescence. RESULTS: In normal animals, the mean values of nitrite/nitrate concentrations in the first microdialysate sample of the cerebrospinal fluid and of the spinal cord interstice were similar (482.5±90.2pmol/75μL, n=20, and 505.7±11.5pmol/75μL, n=6, respectively), whereas, in the samples from rats with cystitis, these values were significantly greater (955.5±66.3pmol/75μL, n=8, and 926.5±131.7pmol/75μL, n=11, respectively). In both groups, NGmonomethyl-L- arginine caused a significant reduction in the nitrite/nitrate concentration. Interestingly, the maximal reduction of nitrite/nitrate concentration caused by NG-monomethyl-L- arginine was no greater than 30% of the initial values. CONCLUSIONS: These results constitute the first demonstration that nitrite/nitrate concentrations in the cerebrospinal fluid and spinal cord interstice are elevated between 20- and 22 hours after cyclophosphamide-induced cystitis, and indicate that cystitis is associated with changes in the production of nitric oxide in the spinal cord segments, where most primary bladder afferents end.